Uncovering the molecular mechanisms of Acer fabri in adjusting to low-temperature stress through integrated physiological and transcriptomic analysis - Gongwei Chen; Dandan Zhang; Fengyuan Chen; Yixiao Zhou; Hongyu Cai; Heng Gu; Yuanzheng Yue; Lianggui Wang; Guohua Liu (Scientific Reports)
Abstract Acer fabri is an excellent color-leaf tree species, with high ornamental value. Low temperatures are known to limit the growth and geographical distribution of A. fabri. The molecular mechanism of A. fabri in response to low-temperature stress was rarely reported. To understand the molecular mechanism of A. fabri in response to low-temperature stress, relevant physiological changes were identified and the transcriptome sequencing was conducted under different stress durations. The results showed that the proline, the soluble sugar (SS) and the soluble protein (SP) content increased in A. fabri leaves under low-temperature stress, while the peroxidase (POD) and activating superoxide dismutase (SOD) activity increased first and then decreased. It was also found by the OPLS-DA analysis that SOD is the most important physiological indicator of A. fabri in response to low-temperature stress. By transcriptome sequencing, a total of 56,732 genes were identified, including 832 transcription factors (TFs). Differentially expressed genes (DEGs) were significantly enriched in metabolic pathways, phytohormone signaling, and plant mitogen-activated protein kinase (MAPK) signaling pathways. Moreover, the analysis of gene co-expression networks, specifically weighted gene co-expression network analysis (WGCNA), indicates that Af0048792 and Af0026061 could be significant in the response to stress from low temperatures. Furthermore, it was observed that NAC (Af0033429) and MIKC (Af0004917) might have interactions with Af0048792, and MIKC (Af0004917) may additionally interact with Af0026061. These findings could enhance our understanding of the molecular mechanisms of A. fabri in response to low-temperature stress.